Circadian rhythmicity of amyloid-beta-related molecules is disrupted in the choroid plexus of a female Alzheimer's disease mouse model - Furtado, André; Esgalhado, André J.; Duarte, Ana C.; Costa, Ana R.; Costa-Brito, Ana R.; Carro, Eva; Ishikawa, Hiroshi; Schroten, Horst; Schwerk, Christian; Gonçalves, Isabel; Arosa, Fernando A.; Santos, Cecília R. A.; et al. (Journal of neuroscience research, 2023)
The choroid plexus (CP) is part of the blood-cerebrospinal fluid barrier (BCSFB) and was recently described as an important component of the circadian clock system. It is the principal source of cerebrospinal fluid (CSF) and responsible for the synthesis and secretion of various neuroprotective peptides including those involved in amyloid-β (Aβ) transport/degradation, contributing to Aβ homeostasis. Inadequate Aβ metabolic clearance and transport across the BCSFB have been associated with circadian dysfunctions in Alzheimer's disease (AD) patients. To investigate whether AD pathology influences Aβ scavengers circadian expression, we collected CP at different time points from an AD mouse model (APP/PS1) (female and male animals, aged 6- and 12-months-old) and analyzed their mRNA expression by Real-time RT-PCR. Only angiotensin-converting enzyme (Ace) expression in 6-month-old female wild-type mice and transthyretin (Ttr) expression in 12-month-old female wild-type mice presented significant rhythmicity. The circadian rhythmicity of Ace and Ttr, prompt us to analyze the involvement of circadian rhythm in Aβ uptake. A human CP papilloma (HIBCPP) cell line was incubated with Aβ-488 and uptake was evaluated at different time points using flow cytometry. Aβ uptake displayed circadian rhythmicity. Our results suggest that AD might affect Aβ scavengers rhythmicity and that Aβ clearance is a rhythmic process possibly regulated by the rhythmic expression of Aβ scavengers.